2022
DOI: 10.2152/jmi.69.112
|View full text |Cite
|
Sign up to set email alerts
|

Follicular fluid 8-Hydroxy-2-Deoxyguanosine (8-OHdG) as biomarker for oxidative stress in intracytoplasmic sperm injection

Abstract: Oxidative stress (OS) is a situation that occurs as a result of un-equilibrium between reactive oxygen species (ROS) formation and the antioxidant defence system. 8-hydroxy-2-deoxyguanosine (8-OHdG), an oxidized form of deoxyguanosine, is found in higher levels in aging oocytes. In this cross-sectional study, we aimed to evaluate the effect of 8-OHdG on the intracytoplasmic sperm injection (ICSI). Follicular fluid (FF) samples were taken after removing the oocyte for later analysis of 8-OHdG. The couples parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…As is well known, inhibiting oxidative stress and cell apoptosis are some potential mechanisms of anti-ischemic drugs, and ginkgolides can achieve this [ 35 ]. We present found that 8-OHdG, a biomarker of oxidative stress [ 36 ], raised in TBI mice, and was inhibited by GA administration. After treatment of GA, the increase of MDA and the decrease of SOD in the brain of TBI were also reversed.…”
Section: Discussionmentioning
confidence: 99%
“…As is well known, inhibiting oxidative stress and cell apoptosis are some potential mechanisms of anti-ischemic drugs, and ginkgolides can achieve this [ 35 ]. We present found that 8-OHdG, a biomarker of oxidative stress [ 36 ], raised in TBI mice, and was inhibited by GA administration. After treatment of GA, the increase of MDA and the decrease of SOD in the brain of TBI were also reversed.…”
Section: Discussionmentioning
confidence: 99%
“…As follicular fluid is closely associated with granulosa cells and oocytes, iron-or oxidative stress-induced proteins (e.g., MDA, 8-OHdG, and ferroportin) may serve as biomarkers for evaluating oocyte quality [73]. Accumulating evidence suggests that the 8-OHdG level in follicular fluid is elevated in women with endometriosis [50] or negatively influences ICSI outcome [99]. The use of such markers in the follicular fluid may afford opportunities to predict and assess infertility outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The development of probes to detect DNA oxidation in the form of 8OHdG has also been used as an oxidative stress biomarker in a reproductive context. For example, the ability of xenobiotics to induce oxidative stress during pregnancy (Lan et al 2022), to monitor the quality of oocytes used in ICSI cycles (Mukheef et al 2022), to evaluate oxidative stress in spermatozoa (Vorilhon et al 2018, Gharagozloo et al 2022, and as a means of determining the reproductive toxicity associated with a wide variety of pollutants including phthalate esters and insecticides (Brassea-Pérez et al 2022, Pan et al 2022.…”
Section: Development Of Biomarkers For Oxidative Stressmentioning
confidence: 99%